Triboelectric Energy Generation for Modulating the Intermodulation of Quartz Oscillators in a Transmitter-to-Receiver System - Wen-Teng Chang; Cheng-Ting Kuo; Ting-He Shen; Hung-Shiu Lin; Yu-Ting Su (IEEE Access, 2022)
A quartz oscillator has a stable frequency that can be tuned by applying a voltage across the quartz crystal. This study applied a triboelectric generator (TEG) as mechanical stimuli on the input voltage of a remote transmitter in a transmitter-to-receiver system. The intermodulation (IM) frequencies were chosen instead of the transmitter frequencies because the IM signals are generally significant. This study first examined the rectified electric voltage from contact-separation and single-electrode mode TEGs. The series connection TEG, stored capacitor, and passive voltage regulator (zener diode) determine the quality of the direct current voltage. The increase in the input voltage via mechanical stimuli on the transmitter was proved to deliver a signal where the IM frequencies increase with the stimuli in the system.